Potential Effects of Myrmecodia Pendants (Ant Nests) on Healing Bone Injuries - Najah, Adilla Syahsiyatun; Kilo, Akram La; Kadir, Ahmad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Myrmecodia pendens is a medical plant that can have a healing effect on bone injuries. Bone injuries can occur due to many things, including injuries due to infection, non-infection, degeneration and neoplasms. Bones are the most important part of the body for the human body because the decreased bone function will affect human activities. Therefore better bone healing is needed. This review article aims to study and analyze the role of Myrmecodia pendens in the bone wound healing process. Several studies show that Myrmecodia pendens contain flavonoids, vitamins, terpenoid saponins, quones, and glycosides, as well as anti-inflammatory substances. These ingredients are markers in the healing process. Myrmecodia pendens has been proven to speed up the healing process. The conclusion shows that Myrmecodia pendens is a medicinal plant that can speed up the healing process of bone injuries.